Pengembangan Media Scrapbook pada Mata Pelajaran IPAS Materi Ekosistem Berbasis Problem Posing untuk Siswa Kelas V SDN 4 Cakranegara - Rubiayanti; Muhammad Erfan; Muhammad Syazali (Mataram University, 2026)
This study aims to describe the development process, validity level, and practicality level of a problem-posing-based scrapbook medium for the Natural and Social Sciences (IPAS) subject on the ecosystem topic for fifth-grade elementary school students. This is a Research and Development (R&D) study adapting Sugiyono's model, limited to seven of ten stages: potential and problems, data collection, product design, design validation, design revision, product trial, and product revision. Research subjects consisted of one subject-matter expert, one media expert, one fifth-grade teacher, and eight fifth-grade students at SDN 4 Cakranegara. Data were collected through questionnaires and documentation and analyzed descriptively based on percentage scores. Results show that the developed medium, covering Chapter 2